ON THE S II AND O I LINE INTENSITIES IN GASEOUS NEBULAE AND NUCLEI OF GALAXIES - PEIMBERT, M (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1979)
We present new photoelectric observations of the [S II] line intensities in the nuclei of M51 and M81. It is shown that the [S II]/[O I] line intensity ratios are very similar in objects where the [O I]/[O III] line intensity ratios differ by as much as t
BOL AGRI
Keywords: LINE INTENSITIES, GASEOUS NEBULAE, NUCLEI, GALAXIES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS